Income Smoothing Practices at Sharia Banks: An Overview in Islamic Business Ethics - Rizkiana Iskandar; Muh. Syahru Ramadhan; Mulyati Mulyati; Chairul Adhim (Profesional Muda Cendekia Publishing, 2022)
Sharia Bank is a bank conducting its business activities based on Islamic principles. Sharia bank as an institution based on the principles of Islam are not allowed to manipulate earnings and engineering activities in any form of earnings management is no exception in terms of financial reporting, which is a medium of information for its users. Income smoothing is an act of deliberate manipulation by management to profits fluctuate, which later reported that corporate profits are at levels considered normal. The purpose of this paper is to investigate the income smoothing practices in sharia banks in Indonesia and review of income smoothing practices according to Islamic business ethics. This study used 11 sharia banks (BUS) based on BUS list on Bank Indonesia's website as research object. To know a company is included in the income smoothing group or not, the Eckel index is used. Based on calculations using Eckel index, it can be concluded that 5 out of 11 sharia banks in Indonesia are indicated to practice income smoothing. However, the annual report of the five syariah banks indicated by the practice of income smoothing indicates that all opinions given by the Sharia Supervisory Board regarding operational activities and products or services provided by sharia banks to customers generally comply with the fatwa and sharia provisions issued by DSN- MUI. That is, the policy or practice of income smoothing in Islamic banks is not contrary to the principles of sharia and Islamic business ethics.